Sonographic Evaluation of Nodules Newly Detected in the Neck After Thyroidectomy: Suture Granuloma Versus Recurrent Carcinoma - Aga, Hitomi; Hirokawa, Mitsuyoshi; Suzuki, Ayana; Ota, Hisashi; Oshita, Maki; Kudo, Takumi; Fukushima, Mitsuhiro; Kobayashi, Kaoru; Miyauchi, Akira (Ultrasound International Open, 2018)
This study aimed to clarify the sonographic features of suture granuloma and recurrent carcinoma newly detected after thyroidectomy.We retrospectively analyzed ultrasound reports with images of 25 cases of suture granuloma and 18 cases of recurrent carcinoma that newly appeared in the resected area after thyroidectomy in our institution. Both suture granulomas and recurrent carcinomas more frequently exhibited multiple lesions rather than solitary lesions. Suture granulomas tended to appear in the more superficial areas than the carotid artery, while recurrent carcinomas were more common between the trachea and carotid artery. A total of 10 of the 11 suture granulomas that we followed up decreased in size. Recurrent carcinomas showed irregular shape (55.6%), taller-than-wide shape (38.9%), low internal echogenicity (83.3%), and no punctate microcalcifications. By contrast, suture granulomas were fusiform in shape (56.0%) and showed linear internal echo parallel to the tissue plane on the longitudinal scan (64.0%). The vascular flow sign was mild to none in the majority of both lesions.Fusiform shape and linear internal echoes indicate suture granuloma, while irregular shape, taller-than-wide shape, and low echogenicity indicate recurrent carcinoma. Given that the clinical management of suture granuloma differs from that of recurrent carcinoma, it is important to distinguish between these two lesions.
Keywords: Thyroid; Suture granuloma; Recurrent carcinoma; Ultrasound; Thyroidectomy